Risk analysis of PM2.5 exposure among workers at railway station - Yuliani, Yeni; Mulyawati, Atikah; Solikhah, Solikhah; Sukesi, Tri Wahyuni (JHeS (Journal of Health Studies), 2025)
Particulate matter 2.5 (PM2.5) is a pollutant that negatively impacts environmental quality and poses health risks to populations exposed over long periods. In Yogyakarta, PM2.5 is the primary pollutant, particularly in urban areas with heavy traffic, such as train stations. This study analyses the risk level of PM2.5 exposure among workers at Yogyakarta Railway Station using an environmental health risk analysis approach. The data was obtained from BB Labkesmas Yogyakarta's study in October 2023, involving 15 respondents working in the station's waiting area. PM2.5 analysis was conducted using a High-Volume Air Sampler (HVAS) with the gravimetric method, and respondents were selected through incidental sampling. The results show that the PM2.5 concentration at Yogyakarta Railway Station (74.97 µg/m³) exceeds the air quality standards set by The Indonesian Ministry of Health Regulation No. 02/2023. Risk analysis calculations indicate that most workers remain within the safe category (HQ ≤ 1) for both a 30-year lifetime exposure projection and a real-time exposure projection. However, a respondent is exposed to an unsafe risk (HQ>1), so precautions must be taken to reduce the risk to a safe level. Additionally, it is necessary to conduct a risk analysis study based on a specific period in the future.